On the use of constrained modulus for soil settlement analysis - Al-Moadhen Muataz Muayad; Abdullah Murtatha M; Oleiwi Mohammed S (Magazine of Civil Engineering, 2024)
Soil settlement is a key parameter in engineering design of geotechnical structures. Two approaches have been used for the characterization of soil behaviour under one dimensional compression: the linear - nonlinear, the traditional approach, and the modulus-based approach, the constrained modulus. The constrained modulus approach requires the knowledge of effective stress ( ), stress exponent ( ), and soil modulus number ( ). In the current study, the constrained modulus approach was adopted in the settlement analysis. Compressibility data of 130 fine and mixed soils with a variety of composition and mineralogy was used in the analysis. In addition, three common clays, bentonite, sepiolite and attapulgite, was experimentally tested using one-dimensional oedometer compression test and the results were included in the analysis. The analysis shows that the approach of constrained modulus can be effectively used to calculate the settlement of fine and intermediate mixed soils, and the stress exponent ( ) varies from 0 for clayey soils to 0.3–0.6 for intermediate silty and clayey sand soils depending on the soil plasticity and particle size distribution. Also, there is a simple relationship with between the soil modulus number, , and the liquid limit, in that the higher the liquid limit, the lower the soil modulus number, .